162k views
2 votes
Solve 23(3x+9)=−2(2x+6).

User Ken Ray
by
5.0k points

2 Answers

5 votes
I think this is the answer. Hope it helps!!!
Solve 23(3x+9)=−2(2x+6).-example-1
User Xeed
by
5.3k points
5 votes
Simplify both sides then distribute.
(23 * 3x) + (23 * 9) = (-2 *2x) + (-2*6)
(69x) + (207) = (-4x) + (-12)
Add the lowest variable to both sides which turns 69x to 73x.
73x +207 = -12
Subtract 207 from both sides.
73x = -219
Divide both sides by 73.
73x/73 = -219/73

Answer: x = -3
User Vass
by
5.0k points